Constraining the growth rate of structure with phase correlations. Issue 2 (13th July 2020) - Byun, Joyce; Franco, Felipe Oliveira; Howlett, Cullan; Bonvin, Camille; Obreschkow, Danail
ABSTRACT: We show that correlations between the phases of the galaxy density field in redshift space provide additional information about the growth rate of large-scale structure that is complementary to the power-spectrum multipoles. In particular, we consider the multipoles of the line correlation function (LCF), which correlates phases between three collinear points, and use the Fisher forecasting method to show that the LCF multipoles can break the degeneracy between the measurement of the growth rate of structure f and the amplitude of perturbations σ8 that is present in the power-spectrum multipoles at large scales. This leads to an improvement in the measurement of f and σ8 by up to 220 per cent for k_max = 0.15 h Mpc^-1 and up to 50 per cent for k_max = 0.30 h Mpc^-1 at redshift z = 0.25, with respect to power-spectrum measurements alone for the upcoming generation of galaxy surveys like DESI and Euclid . The average improvements in the constraints on f and σ8 for k_max = 0.15 h Mpc^-1 are ∼90 per cent for the DESI BGS sample with mean redshift z=0.25, ∼40 per cent for the DESI ELG sample with z=1.25, and ∼40 per cent for the Euclid Hα galaxies with z=1.3 . For k_max = 0.30 h Mpc^-1, the average improvements are ∼40 per cent for the DESI BGS sample and ∼20 per cent for both the DESI ELG and Euclid Hα galaxies.